Repetition of attempted suicide among teenagers in Europe: frequency, timing and risk factors. - Hultén, A; Jiang, G; Wasserman, D; Hawton, K; Hjelmeland, H; De Leo, D; Ostamo, A; Salander-Renberg, E; Schmidtke, A (2001)
BACKGROUND: Adolescents in many countries show high rates of suicide attempts and repetitions of attempts as a common feature. Attempted suicide is the best predictor of future suicide. Repetition of attempts further increases the risk of suicide. The present study sought to identify patterns and risk factors for repetition of attempts in older teenagers. METHODS: Data were collected by uniform procedures in a longitudinal follow-up study in seven European centres participating in the WHO/EURO Multicentre Study on Suicidal Behaviour. Information on attempted suicide in the 15-19-year age group during the period 1989-1995 was analysed. RESULTS: A total of 1,720 attempts by 1,264 individuals over a mean follow-up period of 204 weeks (SD 108.9) were recorded. When life-table analysis was performed, 24% of the individuals who had previously attempted suicide made another attempt within one year after the index attempt, compared with 6.8% of the "first-evers", with no major gender difference. Cox regression analysis revealed that previous attempted suicide (OR 3.3, 95% CI 2.4-4.4) and use of "hard" methods (OR 1.5, 95% CI 1.1-2.1) were both significantly associated with repetition of attempted suicide. Stepwise Cox regression analysis showed that a history of previous attempted suicide was the most important independent predictor of repetition (OR 3.2, 95% CI 2.4-4.4). CONCLUSION: For young suicide attempters, follow-up and adequate aftercare are very important if repetition and risk of suicide are to be reduced. This applies particularly to those who have already made more than one attempt.